Pengaruh Terapi Relaksasi Benson terhadap Tekanan Darah Pasien Hipertensi Intradialitik di RSUD Batang - Nur Khakimah; Dwi Retnaningsih (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Chronic kidney disease (CKD) patients undergoing hemodialysis are at risk of experiencing intradialytic complications, one of which is hypertension. Management of hypertension in hemodialysis units is generally pharmacological, although non-pharmacological interventions may serve as an effective, simple, and safe complementary option. One such technique is Benson relaxation, which combines controlled deep breathing with spiritual elements to reduce sympathetic activity and promote relaxation. This case study to determine the effect of Benson relaxation therapy on blood pressure of intradialytic hypertension patients at RSUD Batang. The case study design was a case study involving 5 CKD patients undergoing hemodialysis. The intervention was performed by guiding patients to practice Benson relaxation for about 10–15 minutes, with blood pressure measured before and after the intervention using a digital sphygmomanometer. The results showed a decrease in blood pressure in most respondents. The average systolic blood pressure decreased from 153.4 mmHg to 145.6 mmHg, while diastolic pressure decreased from 92.4 mmHg to 87.6 mmHg. In addition to physiological improvement, patients also reported subjective relief such as reduced dizziness, palpitations, and tension. In conclusion, Benson relaxation therapy proved effective in reducing blood pressure among intradialytic hypertension patients. This intervention can be recommended as a complementary non-pharmacological therapy in nursing care to improve comfort in hemodialysis patients.